2013
DOI: 10.1111/bph.12108
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the pharmacological profiles of prasugrel and ticagrelor assessed by platelet aggregation, thrombus formation and haemostasis in rats

Abstract: BACKGROUND AND PURPOSEPrasugrel is a third-generation thienopyridine prodrug and ticagrelor is a non-competitive P2Y12 receptor antagonist. In their phase 3 studies, both agents reduced rates of ischemic events relative to treatment with clopidogrel. EXPERIMENTAL APPROACHThe pharmacodynamic profile of anti-platelet effects of prasugrel was compared with that of ticagrelor in rats. KEY RESULTSThe active metabolite of prasugrel was less potent than ticagrelor and its active metabolite on platelet aggregation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
4
21
0
Order By: Relevance
“…Thereby our data confirm and extend in vivo data obtained in animal experiments: Sugidachi and colleagues 16 recently showed that PLT transfusion in rats receiving prasugrel reduced bleeding time, while PLT transfusion did not shorten bleeding time in ticagrelortreated rats.…”
Section: Discussionsupporting
confidence: 91%
“…Thereby our data confirm and extend in vivo data obtained in animal experiments: Sugidachi and colleagues 16 recently showed that PLT transfusion in rats receiving prasugrel reduced bleeding time, while PLT transfusion did not shorten bleeding time in ticagrelortreated rats.…”
Section: Discussionsupporting
confidence: 91%
“…Because of the profound inhibition of platelet aggregation induced by prasugrel, a high platelet transfusion dose also would be required to overcome the effects of prasugrel. Only a single in vivo animal study performed in rats demonstrated that a fixed high dose of allogeneic platelets (increasing the platelet count by 1.6, with no more information regarding platelet count) could shorten but not normalize the bleeding duration after tail transection 4 hours after a loading dose of prasugrel . The result reported herein demonstrates a dose‐effect relationship between the platelet transfusion dose and the reduction of prasugrel‐related bleeding.…”
Section: Discussionmentioning
confidence: 71%
“…There is no direct comparison of dual antiplatelet treatment with aspirin and prasugrel vs. aspirin and ticagrelor in humans, so far. In rats, however, prasugrel and ticagrelor appear to have an equivalent antithrombotic efficacy .…”
Section: Antiplatelet Agentsmentioning
confidence: 90%